2017
DOI: 10.1111/joa.12707
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and development of the extrahepatic biliary system in mouse and rat: a perspective on the evolutionary loss of the gallbladder

Abstract: The gallbladder is the hepatobiliary organ for storing and secreting bile fluid, and is a synapomorphy of extant vertebrates. However, this organ has been frequently lost in several lineages of birds and mammals, including rodents. Although it is known as the traditional problem, the differences in development between animals with and without gallbladders are not well understood. To address this research gap, we compared the anatomy and development of the hepatobiliary systems in mice (gallbladder is present) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
1
27
0
3
Order By: Relevance
“…This organ has a unique smooth muscle layer that produces the contractile movement necessary for bile flow and, phylogenetically, is considered an ancestral character of vertebrates [ 31 ]. However, the gallbladder has been independently lost by many therian mammals and birds for unknown reasons [ 9 , 14 , 30 ]. In the case of mammals, a previous study reported that gallbladder loss occurred due to the loss of the gallbladder–cystic duct domain, which corresponds to the biliary bud in the pharyngula embryo [ 14 ].…”
mentioning
confidence: 99%
“…This organ has a unique smooth muscle layer that produces the contractile movement necessary for bile flow and, phylogenetically, is considered an ancestral character of vertebrates [ 31 ]. However, the gallbladder has been independently lost by many therian mammals and birds for unknown reasons [ 9 , 14 , 30 ]. In the case of mammals, a previous study reported that gallbladder loss occurred due to the loss of the gallbladder–cystic duct domain, which corresponds to the biliary bud in the pharyngula embryo [ 14 ].…”
mentioning
confidence: 99%
“…For this study’s Sprague–Dawley rat model, this modification universally improved the precision of dosimetry models. This is likely due to the fact that, unlike humans, rats have no gallbladder 25 . Consequently, it is important to take into consideration species’ anatomical differences when assessing dosimetry of novel PET radiotracers.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of oxygen consumption by mitochondria was measured by the polarographic method on an LP-7 polarograph using a rotating electrode under standard conditions at 25°C. The ADF/0 and DK ratios were expressed according to Chance-Williams [10][11][12][13][14][15]. Succinate and α-ketoglutarate served as oxidation substrates.…”
Section: Methodsmentioning
confidence: 99%
“…The reducing agent of cytochrome oxidase is cytochrome, located in the intermembrane space. This enzyme combines with oxygen and rapidly reduces oxygen to 2 water molecules [15]. The cytochrome oxidase subunit also interacts with phospholipids of mitochondrial membranes [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation